Lattice structure of the fullerene ferromagnet TDAE-C60 - Stephens, Peter W.; Cox, David; Lauher, Joseph W.; Mihaly, Laszlo; Wiley, John B.; Allemand, P. M.; Hirsch, Andreas; Holczer, Karoly; Li, Q.; Thompson, Joe D.; Wudl, Fred (Nature, 1992)
IN the brief time since the development of techniques for the purification of condensed phases of C (refs 1, 2), compounds of C have been synthesized that exhibit the important solid-state properties of superconductivity and ferromagnetism. The fact that the C molecule participates in these two disparate effects is in itself striking; furthermore, the C-based material has the highest T of any molecular organic ferromagner. An understanding of the physical origin of this ferromagnetism is sure to require a knowledge of the crystal structure. Here we report on an X-ray diffraction study of the ferromagnet TDAE-C, where TDAE is tetrakis(dimethylamino)ethylene, CN(CH). We find that the composition is stoichiometric with 1:1 ratio of TDAE to C. The structure has a c-centred monoclinic unit cell suggestive of an anisotropic, low-dimensional band structure. Any theory for the ferromagnetic behaviour will have to take this anisotropy into account.